The European Union’s strategy of adaptation to the changes taking place in the contemporary international trade (Economic and Political Thought, 2015)
The article raises the issue of transformation in contemporaryinternational trade and its impact on the policy of the European Union.Economic globalisation, global value chains, growing new economic powersthreatened the position of the European Union, which had to choose theright strategy for responding to these changes. Free trade has become theideological determinant of EU policy, which guarantees economic growth inboth developed countries and developing countries. The article consists ofthree parts, introduction and summary. The first part of the article presentsthe implications of globalisation for modern international trade relations.The second part was devoted to the analysis of the Union’s policy towardsthe ongoing transformations. In the third presents the methodology used bythe Union in the implementation of the idea of free trade.